PEMBENTUKAN FORUM KOORDINASI DALAM RANGKA PEMBENAHAN PENGELOLAAN KAWASAN WARISAN BUDAYA DUNIA (WBD) HULU DAS PAKERISAN - W. Windia; Sumiati Sumiati; I.K. Suamba; I. W. Tika; G. Sedana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The existence of green open spaces, especially rice field becomes very important since subak in upstream of Pakerisan watershed area established as one of the world's cultural heritage (WCH) of Bali Province. It is very important is to maintain and manage this site. For that, there should be an inventory of information with interviews, in depth interviews and field surveys and coordination with stakeholders. Furthermore, formulated of subak system empowerment strategies in the world cultural heritage (WCH) upstream Pakerisan site to support sustainability. Based on the SWOT analysis showed that the strategy that should be done is an aggressive strategy. The formulation of activities to implement these strategies include: forming a coordination forum for WCH management, efforts to increase farmers' income, and increase the ability of people to be involved in the development of agro-ecotourism in the site of WCH. The establishment of a coordination forum in the upstream of Pakerisan watershed WCH site involve stakeholders in the site. This coordination forum will be an information center and problem-solving comprehensively institution. Moreover, since recorded as WCH, in the upstream of Pakerisan watershed have some conflict.